Peran dan Tanggung Jawab Kepala SMK Islam Cipasung dalam Meningkatkan Kualitas Akhlak Peserta Didik - Jajang, Jajang; Sri Anggraeni, Ulan; Nurjuman, Iman; Ijudin, Ijudin (Green Publisher Indonesia, 2025)
This study aims to analyze the role and responsibility of the principal of SMK Islam Cipasung in improving the quality of students' morals. The problems faced in the world of education today include the moral degradation and morals of students which require more attention from the leaders of educational institutions. This research is focused on three problem formulations: (1) What are the roles and responsibilities of school principals towards students? (2) How to improve the quality of students' morals at Cipasung Islamic Vocational School? and (3) What is the relationship between the role and responsibility of the principal in improving the quality of students' morals? Through a qualitative approach with a descriptive method, this study explores the views and practices of the principal of SMK Islam Cipasung in moral development. The results of the study show that the role of the principal is very influential on the formation of character and morality of students. The principal is not only responsible as an administrative manager, but also as a spiritual leader who creates an Islamic environment and encourages the integration of moral values in the curriculum. Thus, the role and responsibility of the principal of SMK Islam Cipasung is directly correlated with improving the quality of students' morals.